Nitrogen mineralization and phosphorus solubization due to rewetting of forest and paddy soils - Aragon, Marco Rodel J.; Asio, Victor B. (Annals of Tropical Research, 2010)
Rewetting of soils may cause an increase in phosphorus solubilization and nitrogen mineralization resulting in the release of bioavailable phosphates and nitrate which are vital for crop growth but are also associated with eutrophication of surface waters. The study was conducted to evaluate P solubilization and N mineralization due to drying and rewetting of forest and paddy soils under laboratory conditions. Forest and paddy soils were tested for water extractable P and mineralizable N (NH4 + and NO3–) after being subjected to drying and rewetting cycles for 7 and 14 days of drying. Soil samples were also analyzed for pH, OM, total P, available P, and clay contents. Results indicated a significant increase in water-extractable P and total mineralized N for all the samples tested. N mineralization and P solubilization were correlated with OM, total N, available P, and clay. Findings also revealed that NH4 + concentration increased while that of NO3– decreased significantly for all the samples tested. The amounts of water-extractable P and NO3– released due to rewetting could potentially accelerate eutrophication if transported to bodies of water. They could also however benefit the growing plant.